Isolated Third Metatarsal Fracture, A Rare Case Report with Literature Review - Mohamad Alsamal; Mohammad Ramadan Hazza Hamad; Ahmed Magdy Saleh Mohamed; Syed Imaduddin; Ahmed Alhebshi (Dr. Sulaiman Al Habib Medical Journal)
A 23-year-old man presented to the doctor with swelling and bruising in his left foot following a fall that was caused by plantar flexion and inversion twisting. Radiographic examination revealed an isolated third metatarsal oblique shaft fracture with a 4.4-mm translocation and 5° angulation. The fracture was treated conservatively, based on the patient’s preference, with no further disabling complications and no surgeries, which are usually common. After 16 months of follow-up, the patient regained full foot function and was able to participate in normal life activities without pain or limitation.